Case Report: Type II Bartter syndrome with a novel KCNJ1 variant in a premature neonate presenting with features of salt-wasting congenital adrenal crisis and pseudo-hypoaldosteronism - Tsui, Heung-Ching; Cheng, Hua Tse-Timothy; Lam, Kai-Yee; Leung, Lai-Ting; Au, Ka-Nam; Wong, Wai-Yu; Siu, Luen Yee-Sylvia; Wong, Lap-Ming (Frontiers in Pediatrics, 2025)
IntroductionBartter syndrome (BS) is a rare group of inherited renal tubulopathies. Diagnosis of BS type II is challenging in the neonatal period as its clinical findings and biochemical features may mimic that of adrenal crisis and pseudo-hypoaldosteronism (PHA) initially. Treatment should be instituted immediately for acute adrenal insufficiency as it is a medical emergency, then modified according to available investigation results and treatment response.Case presentationWe describe a premature female neonate with an antenatal history of severe unexplained polyhydramnios, presented with features of adrenal crisis managed with hydrocortisone and fludrocortisone. Initial endocrine investigations excluded salt-wasting congenital adrenal hyperplasia (SW-CAH) and pointed to the diagnosis of PHA with hyperreninemic hyperaldosteronism. Hydrocortisone was gradually weaned off while fludrocortisone was continued for sodium retention effect. Hyperkalemia quickly transited into hypokalemia requiring high potassium requirement. Clinical and biochemical features of BS gradually evolved with polyuria, excessive weight loss, hypochloremic metabolic alkalosis and hypercalciuria at 1 week of age. Urgent trio whole exome sequencing (WES) subsequently confirmed the diagnosis of BS type II where compound heterozygous missense variants were identified in the KCNJ1 gene, one of which was a novel variant. Fludrocortisone was stopped and indomethacin was started with favorable outcomes.ConclusionThough hypokalemia is the key feature of BS, transient hyperkalemia can occur in the early neonatal period in BS type II. Antenatal history should be enquired thoroughly to look for presence of severe unexplained polyhydramnios. The diagnosis of BS type II should be considered if other biochemical features are present. Genetic tests are important to provide a definite diagnosis and guide subsequent management and genetic counselling.